Adults with Down syndrome: a comprehensive approach to manage complexity. Issue 6 (9th January 2019) - Carfì, A.; Vetrano, D. L.; Mascia, D.; Meloni, E.; Villani, E. R.; Acampora, N.; Brandi, V.; Fries, B. E.; Martin, L.; Bernabei, R.; Onder, G.
Abstract: Background: Down syndrome (DS) is characterised by premature ageing that affects selected organ systems, and persons with this condition can present patterns of co‐morbidities and deficits often observed in the older population without DS. However, information on the characteristics of adult persons with DS is limited. The objective of the study is to describe characteristics of adults with DS collected with a standardised, comprehensive assessment instrument. Methods: Cross‐sectional study. Four hundred thirty adults with DS (age range 18/75 years) from three countries (Italy, n = 95; USA, n = 175; and Canada, n = 160). A standardised assessment instrument (interRAI intellectual disability) was used to assess sample characteristics. Results: Mean age ranged from 35.2 (standard deviation 12.0) years in the US sample to 48.8 (standard deviation 9.0) years in the Canadian sample. Most participants in the Italian and US sample were living in private homes, while more than half of those in the Canadian sample were institutionalised. Prevalences of geriatric conditions, including cognitive deficits, disability in the common activities of daily living, symptoms of withdrawal or anhedonia, aggressive behaviour, communication problems, falls and hearing problems were high in the study sample. Gastrointestinal symptoms, skin and dental problems and obesity were also frequently observed. Conclusions: Adults with DS present with a high level of complexity, which may suggest the need for an approach based on a comprehensive assessment and management that can provide adequate care. Further research is needed to understand better the effectiveness of such an approach in the DS population.